Pengaruh Live Streaming Shopping Instagram Terhadap Kepercayaan Konsumen Online dan Dampaknya pada Keputusan Pembelian - Galih Ginanjar Saputra; Fadhilah Fadhilah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Studies have found that social media is an effective marketing medium to influence consumers. In the midst of intense business competition, business actors must keep up-to-date with the development of trends in social media. Live Streaming is a new feature on Instagram that can be used by business people as a marketing strategy. Live Streaming Shopping (LSS) is a new trend that allows business people to interact in real-time directly with consumers. This study aims to analyze the influence of LSS on online consumer trust, to analyze the influence of trust on purchasing decisions, and to analyze the influence of LSS on purchasing decisions either directly or indirectly through trust in social media Instagram. This research was conducted on 109 respondents who have joined and made purchasing decisions through Live Streaming Shopping on Instagram social media. This type of research is carried out using explanatory research, with quantitative methods. Furthermore, the data were analyzed using the Path Analysis technique or path analysis to determine the direct or indirect effect of the variables studied. The results of the study prove that of the four hypotheses proposed in this study, it is stated that the first, second, third, and fourth hypotheses are accepted. The results of this study found that LSS has an influence on online consumer trust and has a positive impact on purchasing decisions. As for the amount of direct influence between live streaming shopping on purchasing decisions, which is 16.9%, while the indirect influence between live streaming shopping on purchasing decisions through online consumer confidence with a magnitude of influence of 52.7% means that the contribution of indirect influence is greater than the contribution of the direct influence of live streaming shopping on purchasing decisions.